Effective Communication Following Pregnancy Loss: A Study in England - Austin, Louise (Cambridge quarterly of healthcare ethics, 2021)
Each year in the UK there are approximately 250,000 miscarriages, 3,000 stillbirths and 3,000 terminations following a diagnosis of fetal-abnormality. This paper draws from original empirical research into the experience of pregnancy loss and the accompanying decisionmaking processes. A key finding is that there is considerable variation across England in the range of options that are offered for disposal of pregnancy remains and the ways in which information around disposal are communicated. This analysis seeks to outline the key features of what constitutes effective communication in this context, where effective communication is taken to mean that patients are provided with the key information necessary, in an appropriate manner, so that they are fully able to make a decision. A primary source of evidence includes interviews with the bereaved and pregnancy-loss support workers, in order to understand how the options available, and associated necessary procedures, are communicated. In addition, patient information leaflets are also analyzed as they offer an important tool for information delivery at a difficult and emotionally charged time. Following this, an overview is provided of the information that these leaflets should contain, along with guidance on effective presentation of this information.